Avitellina Centripunctata Infection In Nilgai Boselaphus Tragocamelus - Kamdi, B. P.; Kulurkar, P. M.; Kurkure, N. V.; Kolte, S. W.; Pande, R.; Raut, S. W.; Bhandarkar, A. G.; Sonkusale , P. M. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The largest species of antilope Nilgai (Boselaphus tragocamelus) is a common wild animal of India and Pakistan. The health condition of the animal is severely affected by various pathogens including parasitic infections. The infection of adult tapeworm parasites in herbivores animals adversely affects the growth, production and immune status of animals. Their systemic study in wild as well as domesticated animals is of upmost importance. Information regarding the prevalence of tape worm infection in Nilgai from Central India is not well documented till date. The present communication deals with the occurrence of tapeworm infection in Nilgai from Central India.